02 Handout 1

Download as pdf or txt
Download as pdf or txt
You are on page 1of 11

GE1703

CONTINUITY ON AN INTERVAL AND DIFFERENTIATION


CONTINUITY ON AN INTERVAL

Definition 2.1 (continuity on an open interval)


A function 𝑓𝑓 is said to be continuous on an open interval if 𝑓𝑓 is continuous at every point on the interval.

Example:
1. Every polynomial function is continuous on any open interval. (This is a consequence of Theorem 1.16.
See Page 15 of 01 Handout 1)

Definition 2.2
A function 𝑓𝑓 is said to be continuous from the right at the number 𝑏𝑏 if and only if the following holds:
• 𝑓𝑓(𝑏𝑏) exists;
• lim+ 𝑓𝑓(𝑥𝑥) exists; and
𝑥𝑥→𝑏𝑏
• lim 𝑓𝑓(𝑥𝑥) = 𝑓𝑓(𝑏𝑏).
𝑥𝑥→𝑏𝑏+

Definition 2.3
A function 𝑓𝑓 is said to be continuous from the left at the number 𝑏𝑏 if and only if the following holds:
• 𝑓𝑓(𝑏𝑏) exists;
• lim− 𝑓𝑓(𝑥𝑥) exists; and
𝑥𝑥→𝑏𝑏
• lim 𝑓𝑓(𝑥𝑥) = 𝑓𝑓(𝑏𝑏).
𝑥𝑥→𝑏𝑏−

Definition 2.4 (continuity on a closed interval)


A function 𝑓𝑓 is said to be continuous on the closed interval [𝑎𝑎, 𝑏𝑏] if:
• 𝑓𝑓 is continuous on the open interval (𝑎𝑎, 𝑏𝑏);
• 𝑓𝑓 is continuous from the right at 𝑎𝑎; and
• 𝑓𝑓 is continuous from the left at 𝑏𝑏.

Example:
1. Every polynomial is continuous on any closed interval.

Definition 2.5 (continuity on a half-open interval)


A function 𝑓𝑓 whose domain includes the interval [𝑎𝑎, 𝑏𝑏) is continuous on [𝑎𝑎, 𝑏𝑏) if and only if:
• 𝑓𝑓 is continuous on the open interval (𝑎𝑎, 𝑏𝑏); and
• 𝑓𝑓 is continuous from the right at 𝑎𝑎.
A function 𝑓𝑓 whose domain includes the interval (𝑎𝑎, 𝑏𝑏] is continuous on (𝑎𝑎, 𝑏𝑏] if and only if:
• 𝑓𝑓 is continuous on the open interval (𝑎𝑎, 𝑏𝑏); and
• 𝑓𝑓 is continuous from the left at 𝑏𝑏.

Example:
1. Every polynomial function is continuous on any half-open interval.

Theorem 2.1 (Intermediate Value Theorem, IVT)


If a function 𝑓𝑓 is continuous on [𝑎𝑎, 𝑏𝑏], and if 𝑓𝑓(𝑎𝑎) ≠ 𝑓𝑓(𝑏𝑏), then for any number 𝑧𝑧 between 𝑓𝑓(𝑎𝑎) and 𝑓𝑓(𝑏𝑏),
there exists a number 𝑐𝑐 between 𝑎𝑎 and 𝑏𝑏 such that 𝑓𝑓(𝑐𝑐) = 𝑧𝑧.
(The proof for this theorem is in the scope of advanced calculus.)

02 Handout 1 *Property of STI


Page 1 of 11
GE1703

Example:
1. Prove that ℎ(𝑥𝑥) = 𝑥𝑥 2 – 𝑥𝑥– 6 has a root on [– 4,0].
Proof:
The function ℎ is a polynomial, and hence continuous on [−4,0]. Moreover, ℎ(−4) = 14 and ℎ(0) = −6.
Since ℎ(0) < 0 < ℎ(−4), by the intermediate value theorem, there exists 𝑐𝑐 ∈ (−4,0) such that ℎ(𝑐𝑐) = 0.

Theorem 2.2 (Squeeze Theorem)


Let 𝑓𝑓, 𝑔𝑔, and ℎ be functions defined on an open interval 𝐾𝐾 except possibly at 𝑎𝑎 (where 𝑎𝑎 ∈ 𝐾𝐾) such that
• 𝑓𝑓(𝑥𝑥) ≤ 𝑔𝑔(𝑥𝑥) ≤ ℎ(𝑥𝑥), for all 𝑥𝑥 ∈ 𝐾𝐾\{𝑎𝑎};
• lim 𝑓𝑓(𝑥𝑥) and lim ℎ(𝑥𝑥) exist; and
𝑥𝑥→𝑎𝑎 𝑥𝑥→𝑎𝑎
• lim 𝑓𝑓(𝑥𝑥) = lim ℎ(𝑥𝑥) = 𝐿𝐿,
𝑥𝑥→𝑎𝑎 𝑥𝑥→𝑎𝑎
then,
• lim 𝑔𝑔(𝑥𝑥) exist; and
𝑥𝑥→𝑎𝑎
• lim 𝑔𝑔(𝑥𝑥) = 𝐿𝐿.
𝑥𝑥→𝑎𝑎

Theorem 2.3
sin 𝜃𝜃
lim =1
𝜃𝜃→0 𝜃𝜃

Theorem 2.4
The sine function is continuous at 0.

Theorem 2.5
The cosine function is continuous at 0.

Theorem 2.6
1 − cos 𝜃𝜃
lim =0
𝜃𝜃→0 𝜃𝜃

The following statements are equivalent:


• lim 𝑓𝑓(𝑥𝑥) = 𝐿𝐿
𝑥𝑥→𝑎𝑎
• lim 𝑓𝑓(𝑥𝑥 + 𝑎𝑎) = 𝐿𝐿
𝑥𝑥→0
• lim [𝑓𝑓(𝑥𝑥) − 𝐿𝐿] = 0
𝑥𝑥→𝑎𝑎

Theorem 2.7
The sine and cosine functions are continuous at every real number.

Theorem 2.8
The tangent, cotangent, secant, and cosecant functions are continuous on their domains.
(The proof is left as an exercise.)

DIFFERENTIATION

Definition 2.6
Any line passing through two points on a curve is called a secant line.

Definition 2.7
Suppose 𝑓𝑓 is continuous at 𝑥𝑥1 . The tangent line to the graph of 𝑓𝑓 at point 𝑃𝑃�𝑥𝑥1 , 𝑓𝑓(𝑥𝑥1 )� is
i. the line through 𝑃𝑃 having slope 𝑚𝑚(𝑥𝑥1 ) given by

02 Handout 1 *Property of STI


Page 2 of 11
GE1703

𝑓𝑓(𝑥𝑥1 + Δ𝑥𝑥) − 𝑓𝑓(𝑥𝑥1 )


𝑚𝑚(𝑥𝑥1 ) = lim
Δ𝑥𝑥→0 Δ𝑥𝑥
if this limit exists;
𝑓𝑓(𝑥𝑥 +Δ𝑥𝑥)−𝑓𝑓(𝑥𝑥1 ) 𝑓𝑓(𝑥𝑥 +Δ𝑥𝑥)−𝑓𝑓(𝑥𝑥1 )
ii. the line 𝑥𝑥 = 𝑥𝑥1 if lim + 1 is +∞ or −∞ and lim− 1 is +∞ or −∞.
Δ𝑥𝑥→0 Δ𝑥𝑥 Δ𝑥𝑥→0 Δ𝑥𝑥
The point 𝑃𝑃�𝑥𝑥1 , 𝑓𝑓(𝑥𝑥1 )� is called the point of tangency.

Definition 2.8
A line perpendicular to the tangent line of a curve of a function 𝑓𝑓 at point 𝑃𝑃 is known as the normal line of
the graph of 𝑓𝑓 at point 𝑃𝑃.

Definition 2.9
The slope of the graph of a function 𝑓𝑓 at a point 𝑃𝑃 is the slope of the tangent line of the graph at 𝑃𝑃.

Definition 2.10
The derivative of a function 𝑓𝑓, denoted by 𝑓𝑓′, is defined as
𝑓𝑓(𝑥𝑥 + Δ𝑥𝑥) − 𝑓𝑓(𝑥𝑥)
𝑓𝑓 ′ (𝑥𝑥) = lim .
Δ𝑥𝑥→0 Δ𝑥𝑥
if the limit exists.

Note that if 𝑥𝑥1 is a particular number in the domain of 𝑓𝑓, then


𝑓𝑓(𝑥𝑥1 + Δ𝑥𝑥) − 𝑓𝑓(𝑥𝑥1 ) (6)
𝑓𝑓 ′ (𝑥𝑥1 ) = lim
Δ𝑥𝑥→0 Δ𝑥𝑥
if the limit exists, which is equal to 𝑚𝑚(𝑥𝑥1 ). Hence, the derivative of 𝑓𝑓 evaluated at 𝑥𝑥1 is precisely the slope
of the tangent line to the graph of a function 𝑓𝑓 at the point �𝑥𝑥1 , 𝑓𝑓(𝑥𝑥1 )�.

Note: Different notations are used in expressing derivatives. Consider a function 𝑓𝑓(𝑥𝑥), the following are the
notations commonly used in this course in expressing the derivative of 𝑓𝑓(𝑥𝑥):
• Leibniz’s notation:
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑(𝑥𝑥) 𝑑𝑑
= (𝑥𝑥) = = 𝑓𝑓(𝑥𝑥)
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
where 𝑦𝑦 = 𝑓𝑓(𝑥𝑥)
• Lagrange’s notation: 𝑓𝑓 ′ (𝑥𝑥)
• Euler’s notation: 𝐷𝐷𝐷𝐷

Examples:
1. Given 𝑔𝑔(𝑥𝑥) = 𝑥𝑥 2 , to solve for 𝑔𝑔′ (𝑥𝑥), we use the definition
𝑔𝑔(𝑥𝑥 + Δ𝑥𝑥) − 𝑔𝑔(𝑥𝑥)
𝑔𝑔′ (𝑥𝑥) = lim
Δ𝑥𝑥→0 Δ𝑥𝑥
(𝑥𝑥 + Δ𝑥𝑥)2 − 𝑥𝑥 2
= lim
Δ𝑥𝑥→0 Δ𝑥𝑥
𝑥𝑥 2 + 2𝑥𝑥Δ𝑥𝑥 + Δ𝑥𝑥 2 − 𝑥𝑥 2
= lim
Δ𝑥𝑥→0 Δ𝑥𝑥
2𝑥𝑥Δ𝑥𝑥 + Δ𝑥𝑥 2
= lim
Δ𝑥𝑥→0 Δ𝑥𝑥
= lim (2𝑥𝑥 + Δ𝑥𝑥)
Δ𝑥𝑥→0
= 2𝑥𝑥
2. To find the equation of the tangent line to the graph of 𝑔𝑔(𝑥𝑥) = 𝑥𝑥 2 at the point �1, 𝑔𝑔(1)�, we use the point-
slope form of the equation of a line given by
𝑦𝑦 − 𝑦𝑦1 = 𝑚𝑚(𝑥𝑥 − 𝑥𝑥1 )
In this case, 𝑥𝑥1 = 1 and 𝑦𝑦1 = 𝑔𝑔(1) = 1. To determine the slope 𝑚𝑚, we evaluate 𝑔𝑔′ (𝑥𝑥) at 1.
𝑔𝑔′ (1) = 2(1) = 2
Therefore, the equation of the tangent line to the graph of 𝑔𝑔 at (1,1) is
𝑦𝑦 − 1 = 2(𝑥𝑥 − 1)

02 Handout 1 *Property of STI


Page 3 of 11
GE1703

𝑦𝑦 − 1 = 2𝑥𝑥 − 2
𝑦𝑦 = 2𝑥𝑥 − 1

Since the derivative of a function is a limit, there will be cases where the limit will not exist, depending on
the value of 𝑥𝑥.

Example:
1
1. Consider solving ℎ′ (𝑥𝑥) where ℎ(𝑥𝑥) = . Using the definition,
𝑥𝑥
ℎ(𝑥𝑥 + Δ𝑥𝑥) − ℎ(𝑥𝑥)
ℎ′ (𝑥𝑥) = lim
Δ𝑥𝑥→0 Δ𝑥𝑥
1 1

= lim 𝑥𝑥 + Δ𝑥𝑥 𝑥𝑥
Δ𝑥𝑥→0 Δ𝑥𝑥
𝑥𝑥 − (𝑥𝑥 + Δ𝑥𝑥)
= lim
Δ𝑥𝑥→0 𝑥𝑥(Δ𝑥𝑥)(𝑥𝑥 + Δ𝑥𝑥)
−Δ𝑥𝑥
= lim
Δ𝑥𝑥→0 𝑥𝑥(Δ𝑥𝑥)(𝑥𝑥 + Δ𝑥𝑥)
1
= lim �− �
Δ𝑥𝑥→0 𝑥𝑥(𝑥𝑥 + Δ𝑥𝑥)
1
At 𝑥𝑥 = 0, the expression − will be undefined. Hence, ℎ′ (0) does not exist.
𝑥𝑥(𝑥𝑥+Δ𝑥𝑥)

An alternative and useful formula for equation (6) can be obtained by letting
𝑥𝑥1 + Δ𝑥𝑥 = 𝑥𝑥.
Hence, Δ𝑥𝑥 → 0 is equivalent to 𝑥𝑥 → 𝑥𝑥1 , and equation (6) is now equivalent to
𝑓𝑓(𝑥𝑥) − 𝑓𝑓(𝑥𝑥1 ) (7)
𝑓𝑓 ′ (𝑥𝑥1 ) = lim
𝑥𝑥→𝑥𝑥1 𝑥𝑥 − 𝑥𝑥1

Definition 2.11
A function 𝑓𝑓 is said to be differentiable at 𝑥𝑥0 if 𝑓𝑓’(𝑥𝑥0 ) exists. If 𝑓𝑓 is differentiable at any point on an open
interval (𝑎𝑎, 𝑏𝑏), then 𝑓𝑓 is said to be differentiable on (𝑎𝑎, 𝑏𝑏). If 𝑓𝑓 is differentiable at any point on its domain,
then 𝑓𝑓 is a differentiable function.

Theorem 2.11
If 𝑓𝑓 is differentiable at 𝑥𝑥1 , then 𝑓𝑓 is continuous at 𝑥𝑥1 .

Note that the converse does not hold.

Definition 2.12
If 𝑓𝑓 is defined at 𝑥𝑥1 , the derivative from the right of 𝑓𝑓 at 𝑥𝑥1 is defined by
𝑓𝑓(𝑥𝑥1 + Δ𝑥𝑥) − 𝑓𝑓(𝑥𝑥1 ) 𝑓𝑓(𝑥𝑥) − 𝑓𝑓(𝑥𝑥1 )
𝑓𝑓+′ (𝑥𝑥1 ) = lim+ = lim+
Δ𝑥𝑥→0 Δ𝑥𝑥 𝑥𝑥→𝑥𝑥1 𝑥𝑥 − 𝑥𝑥1
The derivative from the left of 𝑓𝑓 at 𝑥𝑥1 , is defined by
𝑓𝑓(𝑥𝑥1 + Δ𝑥𝑥) − 𝑓𝑓(𝑥𝑥1 ) 𝑓𝑓(𝑥𝑥) − 𝑓𝑓(𝑥𝑥1 )
𝑓𝑓−′ (𝑥𝑥1 ) = lim− = lim−
Δ𝑥𝑥→0 Δ𝑥𝑥 𝑥𝑥→𝑥𝑥1 𝑥𝑥 − 𝑥𝑥1

A function 𝑓𝑓 fails to be differentiable at a number 𝑎𝑎 falls to only one of these categories:


CASE 1. 𝑓𝑓 is discontinuous at 𝑥𝑥 = 𝑎𝑎;
CASE 2. 𝑓𝑓 has a vertical tangent line at 𝑥𝑥 = 𝑎𝑎; or
CASE 3. 𝑓𝑓 does not have a tangent line at 𝑥𝑥 = 𝑎𝑎.

Theorem 2.12
i. If 𝑓𝑓(𝑥𝑥) = 𝑐𝑐 where 𝑐𝑐 is a constant, then 𝑓𝑓 ′ (𝑥𝑥) = 0.
ii. If 𝑛𝑛 is a positive integer and if 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 𝑛𝑛 , then 𝑓𝑓 ′ (𝑥𝑥) = 𝑛𝑛𝑥𝑥 𝑛𝑛−1 .
iii. If 𝑓𝑓 is differentiable and 𝑔𝑔(𝑥𝑥) = 𝑐𝑐𝑐𝑐(𝑥𝑥), where 𝑐𝑐 is a constant, then 𝑔𝑔′ (𝑥𝑥) = 𝑐𝑐𝑓𝑓 ′ (𝑥𝑥).

02 Handout 1 *Property of STI


Page 4 of 11
GE1703

Theorem 2.13 (Sum Rule of Differentiation)


If 𝑓𝑓 and 𝑔𝑔 are differentiable functions and ℎ is defined by
ℎ(𝑥𝑥) = 𝑓𝑓(𝑥𝑥) + 𝑔𝑔(𝑥𝑥)
then, ℎ′ (𝑥𝑥) = 𝑓𝑓 ′ (𝑥𝑥) + 𝑔𝑔′ (𝑥𝑥).

Theorem 2.14 (Product Rule of Differentiation)


If 𝑓𝑓 and 𝑔𝑔 are differentiable functions and ℎ is defined by
ℎ(𝑥𝑥) = 𝑓𝑓(𝑥𝑥)𝑔𝑔(𝑥𝑥)
then, ℎ′ (𝑥𝑥) = 𝑓𝑓(𝑥𝑥)𝑔𝑔′ (𝑥𝑥) + 𝑔𝑔(𝑥𝑥)𝑓𝑓 ′ (𝑥𝑥).

Example:
Solve for the derivative of the following functions:
1. 𝑝𝑝(𝑥𝑥) = (𝑥𝑥 + 1)(𝑥𝑥 2 + 1)
2. 𝑞𝑞(𝑥𝑥) = (2𝑥𝑥 3 − 4𝑥𝑥 2 )(3𝑥𝑥 5 + 𝑥𝑥 2 )
Solution:
1. Let 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 + 1 and 𝑔𝑔(𝑥𝑥) = 𝑥𝑥 2 + 1. Then 𝑓𝑓 ′ (𝑥𝑥) = 1 and 𝑔𝑔′ (𝑥𝑥) = 2𝑥𝑥. Therefore,
𝑝𝑝′ (𝑥𝑥) = 𝑓𝑓(𝑥𝑥)𝑔𝑔′ (𝑥𝑥) + 𝑔𝑔(𝑥𝑥)𝑓𝑓 ′ (𝑥𝑥)
= (𝑥𝑥 + 1)(2𝑥𝑥) + (𝑥𝑥 2 + 1)(1)
= 3𝑥𝑥 2 + 2𝑥𝑥 + 1
2. Let 𝑓𝑓(𝑥𝑥) = 2𝑥𝑥 3 − 4𝑥𝑥 2 and 𝑔𝑔(𝑥𝑥) = 3𝑥𝑥 5 + 𝑥𝑥 2 . Then 𝑓𝑓 ′ (𝑥𝑥) = 6𝑥𝑥 2 − 8𝑥𝑥 and 𝑔𝑔′ (𝑥𝑥) = 15𝑥𝑥 4 + 2𝑥𝑥. Therefore,
𝑞𝑞′ (𝑥𝑥) = 𝑓𝑓(𝑥𝑥)𝑔𝑔′ (𝑥𝑥) + 𝑔𝑔(𝑥𝑥)𝑓𝑓 ′ (𝑥𝑥)
= (2𝑥𝑥 3 − 4𝑥𝑥 2 )(15𝑥𝑥 4 + 2𝑥𝑥) + (3𝑥𝑥 5 + 𝑥𝑥 2 )(6𝑥𝑥 2 − 8𝑥𝑥)
= (30𝑥𝑥 7 − 60𝑥𝑥 6 + 4𝑥𝑥 4 − 8𝑥𝑥 3 ) + (18𝑥𝑥 7 − 24𝑥𝑥 6 + 6𝑥𝑥 4 − 8𝑥𝑥 3 )
= 48𝑥𝑥 7 − 84𝑥𝑥 6 + 10𝑥𝑥 4 − 16𝑥𝑥 3

Theorem 2.15 (Quotient Rule of Differentiation)


If 𝑓𝑓 and 𝑔𝑔 are differentiable functions, and ℎ is defined by
𝑓𝑓(𝑥𝑥)
ℎ(𝑥𝑥) = , 𝑔𝑔(𝑥𝑥) ≠ 0
𝑔𝑔(𝑥𝑥)
then
𝑔𝑔(𝑥𝑥)𝑓𝑓 ′ (𝑥𝑥) − 𝑓𝑓(𝑥𝑥)𝑔𝑔′ (𝑥𝑥)
ℎ′ (𝑥𝑥) =
[𝑔𝑔(𝑥𝑥)]2

Example:
Solve for the derivative of the following function:
2𝑥𝑥 3 + 4
𝑚𝑚(𝑥𝑥) = 2
𝑥𝑥 + 1
Solution:
Let 𝑓𝑓(𝑥𝑥) = 2𝑥𝑥 3 + 4 and 𝑔𝑔(𝑥𝑥) = 𝑥𝑥 2 + 1. Note that 𝑔𝑔(𝑥𝑥) cannot equal 0 for any real number 𝑥𝑥. The derivatives
are given by 𝑓𝑓 ′ (𝑥𝑥) = 6𝑥𝑥 2 and 𝑔𝑔′ (𝑥𝑥) = 2𝑥𝑥. Therefore,
𝑔𝑔(𝑥𝑥)𝑓𝑓 ′ (𝑥𝑥) − 𝑓𝑓(𝑥𝑥)𝑔𝑔′ (𝑥𝑥)
𝑚𝑚′ (𝑥𝑥) =
[𝑔𝑔(𝑥𝑥)]2
(𝑥𝑥 + 1)(6𝑥𝑥 2 ) − (2𝑥𝑥 3 + 4)(2𝑥𝑥)
2
=
(𝑥𝑥 2 + 1)2
(6𝑥𝑥 4 + 6𝑥𝑥 2 ) − (4𝑥𝑥 4 + 8𝑥𝑥)
=
(𝑥𝑥 2 + 1)2
2𝑥𝑥 + 6𝑥𝑥 2 − 8𝑥𝑥
4
=
(𝑥𝑥 2 + 1)2

Theorem 2.16
If 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 −𝑛𝑛 , where −𝑛𝑛 is a negative integer and 𝑥𝑥 ≠ 0, then 𝑓𝑓 ′ (𝑥𝑥) = −𝑛𝑛𝑥𝑥 −𝑛𝑛−1 .

02 Handout 1 *Property of STI


Page 5 of 11
GE1703

Example:
3
Find the derivative of 𝑓𝑓(𝑥𝑥) = 5.
𝑥𝑥
Solution:
𝑓𝑓(𝑥𝑥) = 3𝑥𝑥 −5
′ (𝑥𝑥)
𝑓𝑓 = 3(−5𝑥𝑥 −6 )
= −15𝑥𝑥 −6

The Chain Rule of Differentiation


If the function 𝑔𝑔 is differentiable at 𝑥𝑥 and the function 𝑓𝑓 is differentiable at 𝑔𝑔(𝑥𝑥), then 𝑓𝑓 ∘ 𝑔𝑔 is differentiable
at 𝑥𝑥, and (𝑓𝑓 ∘ 𝑔𝑔)′ (𝑥𝑥) = 𝑓𝑓 ′ �𝑔𝑔(𝑥𝑥)�𝑔𝑔′ (𝑥𝑥).

Theorem 2.18
𝑚𝑚 𝑚𝑚
𝑚𝑚
If 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 𝑛𝑛 , where 𝑚𝑚 and 𝑛𝑛 are integers and 𝑛𝑛 ≠ 0, then 𝑓𝑓 ′ (𝑥𝑥) = 𝑥𝑥 𝑛𝑛 −1 .
𝑛𝑛

Example:
Find the derivative of ℎ(𝑥𝑥) = √𝑥𝑥 2 + 𝑥𝑥.
Solution:
1
Let 𝑓𝑓(𝑥𝑥) = √𝑥𝑥 = 𝑥𝑥 2 and 𝑔𝑔(𝑥𝑥) = 𝑥𝑥 2 + 𝑥𝑥. Then ℎ(𝑥𝑥) = (𝑓𝑓 ∘ 𝑔𝑔)(𝑥𝑥) and
ℎ′ (𝑥𝑥) = 𝑓𝑓 ′ �𝑔𝑔(𝑥𝑥)�𝑔𝑔′ (𝑥𝑥)
Since
1 1
𝑓𝑓 ′ (𝑥𝑥) = 𝑥𝑥 2−1
2
1 −1
= 𝑥𝑥 2
2
1
= 1
2𝑥𝑥 2
1
=
2√𝑥𝑥
and
𝑔𝑔′ (𝑥𝑥) = 2𝑥𝑥 + 1
then,
ℎ′ (𝑥𝑥) = 𝑓𝑓 ′ (𝑥𝑥 2 + 2𝑥𝑥)𝑔𝑔′ (𝑥𝑥)
2𝑥𝑥 + 1
=
2√𝑥𝑥 2 + 2𝑥𝑥

The following theorem gives the derivatives of the six (6) basic trigonometric functions.

Derivatives of Trigonometric Functions


Consider a differentiable function 𝑢𝑢 = 𝑓𝑓(𝑥𝑥), then the following holds:
𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑 𝑑𝑑𝑑𝑑
sin 𝑢𝑢 = cos 𝑢𝑢 ⋅ cot 𝑢𝑢 = − csc 2 𝑢𝑢 ⋅
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑 𝑑𝑑𝑑𝑑
cos 𝑢𝑢 = − sin 𝑢𝑢 ⋅ sec 𝑢𝑢 = sec 𝑢𝑢 tan 𝑢𝑢 ⋅
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑 2
𝑑𝑑𝑑𝑑 𝑑𝑑 𝑑𝑑𝑑𝑑
tan 𝑢𝑢 = sec 𝑢𝑢 ⋅ csc 𝑢𝑢 = − csc 𝑢𝑢 cot 𝑢𝑢 ⋅
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑

Examples:
Solve for the derivatives of the following functions:
1. 𝑓𝑓(𝑥𝑥) = sec 3 𝑥𝑥
3𝑥𝑥 2
2. 𝑔𝑔(𝑥𝑥) =
cot 𝑥𝑥+1
3. ℎ(𝑥𝑥) = sin(2𝑥𝑥 + 1) cos(2𝑥𝑥 + 1)

02 Handout 1 *Property of STI


Page 6 of 11
GE1703

Solutions:
1. We can let
𝑑𝑑𝑑𝑑
𝑢𝑢 = sec 𝑥𝑥, = sec 𝑥𝑥 tan 𝑥𝑥.
𝑑𝑑𝑑𝑑
Therefore,
𝑓𝑓(𝑥𝑥) = sec 3 𝑥𝑥
= 𝑢𝑢3
Differentiating both sides (applying the power rule and chain rule),
𝑑𝑑 𝑑𝑑𝑑𝑑
𝑓𝑓(𝑥𝑥) = 3𝑢𝑢2 ⋅
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑
Substituting the values of 𝑢𝑢 and ,
𝑑𝑑𝑑𝑑
𝑑𝑑 2 (sec
𝑓𝑓(𝑥𝑥) = 3(sec 𝑥𝑥) ⋅ 𝑥𝑥 tan 𝑥𝑥)
𝑑𝑑𝑑𝑑
3
= 3 sec 𝑥𝑥 tan 𝑥𝑥
2. We can let
𝑑𝑑𝑑𝑑
𝑢𝑢 = 3𝑥𝑥 2 , = 6𝑥𝑥; and
𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑
𝑣𝑣 = cot 𝑥𝑥 + 1, = − csc 2 𝑥𝑥.
𝑑𝑑𝑑𝑑
Hence,
𝑢𝑢
𝑔𝑔(𝑥𝑥) =
𝑣𝑣
Applying the quotient rule,
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑 𝑣𝑣 − 𝑢𝑢
𝑔𝑔(𝑥𝑥) = 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 𝑣𝑣 2
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
Substituting the values of 𝑢𝑢, 𝑣𝑣, , and ,
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑 (cot 𝑥𝑥 + 1)(6𝑥𝑥) − 3𝑥𝑥 2 (− csc 2 𝑥𝑥)
𝑔𝑔(𝑥𝑥) =
𝑑𝑑𝑑𝑑 (cot 𝑥𝑥 + 1)2
6𝑥𝑥 cot 𝑥𝑥 + 6𝑥𝑥 + 3𝑥𝑥 2 csc 2 𝑥𝑥
=
(cot 𝑥𝑥 + 1)2
3. We can let
𝑑𝑑𝑑𝑑
𝑢𝑢 = 2𝑥𝑥 + 1, = 2.
𝑑𝑑𝑑𝑑
Hence,
ℎ(𝑥𝑥) = sin 𝑢𝑢 cos 𝑢𝑢
Differentiating both sides (applying product rule and chain rule),
𝑑𝑑 𝑑𝑑 𝑑𝑑
ℎ(𝑥𝑥) = sin 𝑢𝑢 � cos 𝑢𝑢� + cos 𝑢𝑢 � sin 𝑢𝑢�
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
= sin 𝑢𝑢 �− sin 𝑢𝑢 ⋅ � + cos 𝑢𝑢 �cos 𝑢𝑢 ⋅ �
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑
Substituting the values of 𝑢𝑢 and ,
𝑑𝑑𝑑𝑑
𝑑𝑑
ℎ(𝑥𝑥) = sin(2𝑥𝑥 + 1) (− sin(2𝑥𝑥 + 1) ⋅ 2) + cos(2𝑥𝑥 + 1) (cos(2𝑥𝑥 + 1) ⋅ 2)
𝑑𝑑𝑑𝑑
= −2 sin2 (2𝑥𝑥 + 1) + 2 cos2 (2𝑥𝑥 + 1)

Derivatives of Inverse Trigonometric Functions


Consider a differentiable function 𝑢𝑢 = 𝑓𝑓(𝑥𝑥), the following holds:
𝑑𝑑 1 𝑑𝑑𝑑𝑑 𝑑𝑑 1 𝑑𝑑𝑑𝑑
sin−1 𝑢𝑢 = ⋅ cot −1 𝑢𝑢 = − 2

𝑑𝑑𝑑𝑑 √1 − 𝑢𝑢 𝑑𝑑𝑑𝑑
2 𝑑𝑑𝑑𝑑 1 + 𝑢𝑢 𝑑𝑑𝑑𝑑
𝑑𝑑 −1
1 𝑑𝑑𝑑𝑑 𝑑𝑑 −1
1 𝑑𝑑𝑑𝑑
cos 𝑢𝑢 = − ⋅ sec 𝑢𝑢 = ⋅
𝑑𝑑𝑑𝑑 √1 − 𝑢𝑢 𝑑𝑑𝑑𝑑
2 𝑑𝑑𝑑𝑑 𝑢𝑢√𝑢𝑢 − 1 𝑑𝑑𝑑𝑑
2
𝑑𝑑 −1
1 𝑑𝑑𝑑𝑑 𝑑𝑑 −1
1 𝑑𝑑𝑑𝑑
tan 𝑢𝑢 = 2
⋅ csc 𝑢𝑢 = − ⋅
𝑑𝑑𝑑𝑑 1 + 𝑢𝑢 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑢𝑢√𝑢𝑢2 − 1 𝑑𝑑𝑑𝑑

02 Handout 1 *Property of STI


Page 7 of 11
GE1703

Examples:
Solve for the derivatives of the following functions:
1. 𝑓𝑓(𝑥𝑥) = sin−1 (𝑥𝑥 2 )
2. 𝑔𝑔(𝑥𝑥) = cos(cot −1 𝑥𝑥)
3. ℎ(𝑥𝑥) = 3(cos −1 𝑥𝑥)2
Solutions:
𝑑𝑑𝑑𝑑
1. Let 𝑢𝑢 = 𝑥𝑥 2 , = 2𝑥𝑥. Then
𝑑𝑑𝑑𝑑
𝑓𝑓(𝑥𝑥) = sin−1 𝑢𝑢
Differentiating both sides,
𝑑𝑑 1 𝑑𝑑𝑑𝑑
𝑓𝑓(𝑥𝑥) = ⋅
𝑑𝑑𝑑𝑑 √1 − 𝑢𝑢 𝑑𝑑𝑑𝑑
2
𝑑𝑑𝑑𝑑
Substituting the values of 𝑢𝑢 and ,
𝑑𝑑𝑑𝑑
𝑑𝑑 1
𝑓𝑓(𝑥𝑥) = ⋅ 2𝑥𝑥
𝑑𝑑𝑑𝑑 �1 − (𝑥𝑥 2 )2
2𝑥𝑥
=
√1 − 𝑥𝑥 4
𝑑𝑑𝑑𝑑 1
2. Let 𝑢𝑢 = cot −1 𝑥𝑥, = − . Then
𝑑𝑑𝑑𝑑 1+𝑥𝑥 2
𝑔𝑔(𝑥𝑥) = cos 𝑢𝑢
𝑑𝑑 𝑑𝑑𝑑𝑑
𝑔𝑔(𝑥𝑥) = − sin 𝑢𝑢 ⋅
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
1
= − sin(cot −1 𝑥𝑥) ⋅ �− �
1 + 𝑥𝑥 2
−1
sin(cot 𝑥𝑥)
=
1 + 𝑥𝑥 2
𝑑𝑑𝑑𝑑 1
3. Let 𝑢𝑢 = cos −1 𝑥𝑥, = − . Then
𝑑𝑑𝑑𝑑 �1−𝑥𝑥2

𝑔𝑔(𝑥𝑥) = 3𝑢𝑢2
𝑑𝑑 𝑑𝑑𝑑𝑑
𝑔𝑔(𝑥𝑥) = 6𝑢𝑢 ⋅
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
1
= 6 cos−1 𝑥𝑥 ⋅ �− �
√1 − 𝑥𝑥 2
−1
6 cos 𝑥𝑥
=−
√1 − 𝑥𝑥 2

Derivatives of Exponential and Logarithmic Functions


Let 𝑢𝑢 = 𝑓𝑓(𝑥𝑥) be a differentiable function and 𝑎𝑎 be any positive real number. Then
𝑑𝑑 1 𝑑𝑑𝑑𝑑
log a 𝑢𝑢 = ⋅
𝑑𝑑𝑑𝑑 (ln 𝑎𝑎)𝑢𝑢 𝑑𝑑𝑑𝑑
𝑑𝑑 𝑢𝑢 𝑑𝑑𝑑𝑑
𝑎𝑎 = (ln 𝑎𝑎)𝑎𝑎𝑢𝑢 ⋅
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑 𝑢𝑢 𝑢𝑢
𝑑𝑑𝑑𝑑
𝑒𝑒 = 𝑒𝑒 ⋅
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑

Examples:
Solve for the derivatives of the following functions:
1. 𝑓𝑓(𝑥𝑥) = 4sin 2𝑥𝑥
log 𝑥𝑥
2. 𝑔𝑔(𝑥𝑥) = 10
𝑥𝑥
2
3. ℎ(𝑥𝑥) = sec 3𝑥𝑥

02 Handout 1 *Property of STI


Page 8 of 11
GE1703

Solutions:
1. Let 𝑢𝑢 = sin 2𝑥𝑥. Then
𝑑𝑑𝑑𝑑 𝑑𝑑
= cos 2𝑥𝑥 ⋅ (2𝑥𝑥)
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
= 2 cos 2𝑥𝑥
Rewriting 𝑓𝑓(𝑥𝑥) in terms of 𝑢𝑢,
𝑓𝑓(𝑥𝑥) = 4𝑢𝑢
Differentiating,
𝑑𝑑 𝑑𝑑𝑑𝑑
𝑓𝑓(𝑥𝑥) = (ln 4)4𝑢𝑢 ⋅
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
= (ln 4)4sin 2𝑥𝑥 ⋅ 2 cos 2𝑥𝑥
= 2 ln 4 ⋅ (4sin 2𝑥𝑥 cos 2𝑥𝑥)
2. Let
𝑑𝑑𝑑𝑑 1
𝑢𝑢 = log10 𝑥𝑥, = (ln ;
𝑑𝑑𝑑𝑑 10)𝑥𝑥
𝑑𝑑𝑑𝑑
𝑣𝑣 = 𝑥𝑥, = 1.
𝑑𝑑𝑑𝑑
𝑢𝑢
Therefore, 𝑔𝑔(𝑥𝑥) = . Applying the quotient rule,
𝑣𝑣
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑 𝑣𝑣 − 𝑢𝑢
𝑔𝑔(𝑥𝑥) = 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 𝑣𝑣 2
1
𝑥𝑥 � � − log10 𝑥𝑥
(ln 10)𝑥𝑥
=
𝑥𝑥 2
1
− log10 𝑥𝑥
= ln 10 2
𝑥𝑥
ln 𝑎𝑎 ln 𝑥𝑥
Recall that log 𝑎𝑎 𝑏𝑏 = . Hence, log10 𝑥𝑥 = . Therefore,
ln 𝑏𝑏 ln 10
1 ln 𝑥𝑥
𝑑𝑑 −
𝑔𝑔(𝑥𝑥) = ln 10 2 ln 10
𝑑𝑑𝑑𝑑 𝑥𝑥
1 − ln 𝑥𝑥
=
(ln 10)𝑥𝑥 2
𝑥𝑥 2
3. Let 𝑢𝑢 = 3 . Then
𝑑𝑑𝑑𝑑 2 𝑑𝑑 2
= (ln 3)3𝑥𝑥 ⋅ 𝑥𝑥
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
2
= (ln 3)3𝑥𝑥 ⋅ 2𝑥𝑥
2
= (2 ln 3)𝑥𝑥3𝑥𝑥
Therefore,
ℎ(𝑥𝑥) = sec 𝑢𝑢
𝑑𝑑 𝑑𝑑𝑑𝑑
ℎ(𝑥𝑥) = sec 𝑢𝑢 tan 𝑢𝑢 ⋅
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
2 2 2
= sec 3𝑥𝑥 tan 3𝑥𝑥 ⋅ (2 ln 3)𝑥𝑥3𝑥𝑥
2 2 2
= (2 ln 3)𝑥𝑥3𝑥𝑥 sec 3𝑥𝑥 tan 3𝑥𝑥 ⋅

HIGHER ORDER DERIVATIVES

If the function 𝑓𝑓 is differentiable, its derivative 𝑓𝑓′ is sometimes called the first derivative of 𝑓𝑓. If the function
𝑓𝑓′ is again differentiable, its derivative 𝑓𝑓′′ (read as 𝑓𝑓 double prime) is called the second derivative. The
process of differentiation can be carried over as long as the resulting derivatives are again differentiable.
The 𝑛𝑛𝑡𝑡ℎ derivatia ve of the function 𝑓𝑓, where 𝑛𝑛 is a positive number greater than 1 is the derivative of the
(𝑛𝑛 − 1)𝑡𝑡ℎ derivative. The following are the notations for the higher order derivatives:
• Leibniz’s notation:
𝑑𝑑 2 𝑑𝑑 3 𝑑𝑑 4 𝑑𝑑 𝑛𝑛
� � 𝑓𝑓(𝑥𝑥), � � 𝑓𝑓(𝑥𝑥), � � 𝑓𝑓(𝑥𝑥), … , � � 𝑓𝑓(𝑥𝑥)
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
or

02 Handout 1 *Property of STI


Page 9 of 11
GE1703

𝑑𝑑 2 𝑦𝑦 𝑑𝑑 3 𝑦𝑦 𝑑𝑑 4 𝑦𝑦 𝑑𝑑 𝑛𝑛 𝑦𝑦
, , , … ,
𝑑𝑑𝑥𝑥 2 𝑑𝑑𝑥𝑥 3 𝑑𝑑𝑥𝑥 4 𝑑𝑑𝑥𝑥 𝑛𝑛
where 𝑦𝑦 = 𝑓𝑓(𝑥𝑥)
• Lagrange’s notation: 𝑓𝑓 ′′ (𝑥𝑥), 𝑓𝑓 ′′′ (𝑥𝑥), 𝑓𝑓 (4) (𝑥𝑥), … , 𝑓𝑓 (𝑛𝑛) (𝑥𝑥)
• Euler’s notation: 𝐷𝐷 2 𝑓𝑓, 𝐷𝐷 3 𝑓𝑓, 𝐷𝐷 4 𝑓𝑓, … , 𝐷𝐷 𝑛𝑛 𝑓𝑓

Examples:
1. Let
a. 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 5 + 5𝑥𝑥 4 + 10𝑥𝑥 3 + 10𝑥𝑥 2 + 5𝑥𝑥 + 1
b. 𝑔𝑔(𝑥𝑥) = cos 𝑥𝑥 + sin 𝑥𝑥
c. ℎ(𝑥𝑥) = 𝑒𝑒 3𝑥𝑥 + 1
𝑑𝑑 3 𝑑𝑑 3 𝑑𝑑 3
Find � � 𝑓𝑓(𝑥𝑥), � � 𝑔𝑔(𝑥𝑥), and � � ℎ(𝑥𝑥).
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
Solution:
a.
𝑑𝑑
𝑓𝑓(𝑥𝑥) = 5𝑥𝑥 4 + 20𝑥𝑥 3 + 30𝑥𝑥 2 + 20𝑥𝑥 + 5
𝑑𝑑𝑑𝑑
𝑑𝑑 2
� � 𝑓𝑓(𝑥𝑥) = 20𝑥𝑥 3 + 60𝑥𝑥 2 + 60𝑥𝑥 + 20
𝑑𝑑𝑑𝑑
𝑑𝑑 3
� � 𝑓𝑓(𝑥𝑥) = 60𝑥𝑥 2 + 120𝑥𝑥 + 60
𝑑𝑑𝑑𝑑
b.
𝑑𝑑
𝑔𝑔(𝑥𝑥) = − sin 𝑥𝑥 + cos 𝑥𝑥
𝑑𝑑𝑑𝑑
𝑑𝑑 2
� � 𝑔𝑔(𝑥𝑥) = − cos 𝑥𝑥 − sin 𝑥𝑥
𝑑𝑑𝑑𝑑
𝑑𝑑 3
� � 𝑔𝑔(𝑥𝑥) = sin 𝑥𝑥 − cos 𝑥𝑥
𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑
c. Let 𝑢𝑢 = 3𝑥𝑥, = 3. Then
𝑑𝑑𝑑𝑑
𝑑𝑑 𝑑𝑑 𝑢𝑢
ℎ(𝑥𝑥) = (𝑒𝑒 + 1)
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑
= 𝑒𝑒 𝑢𝑢
𝑑𝑑𝑑𝑑
= 3𝑒𝑒 𝑢𝑢
𝑑𝑑 2 𝑑𝑑
� � ℎ(𝑥𝑥) = 3 𝑒𝑒 𝑢𝑢
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑
= 3𝑒𝑒 𝑢𝑢 ⋅
𝑑𝑑𝑑𝑑
= 9𝑒𝑒 𝑢𝑢
𝑑𝑑 3 𝑑𝑑
� � ℎ(𝑥𝑥) = 9 𝑒𝑒 𝑢𝑢
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑
= 9𝑒𝑒 𝑢𝑢 ⋅
𝑑𝑑𝑑𝑑
= 27𝑒𝑒 𝑢𝑢
Therefore,
𝑑𝑑 3
� � ℎ(𝑥𝑥) = 27𝑒𝑒 3𝑥𝑥
𝑑𝑑𝑑𝑑

02 Handout 1 *Property of STI


Page 10 of 11
GE1703

The Indian mathematician Bhāskara II (1114–1185) is credited with knowledge of the theorem below.
Although the theorem is named after Michel Rolle.

Theorem 2.22 (Rolle’s Theorem)


Let 𝑓𝑓 be a function satisfying the following conditions:
• 𝑓𝑓 is continuous on the closed interval [𝑎𝑎, 𝑏𝑏]
• 𝑓𝑓 is differentiable on the open interval (𝑎𝑎, 𝑏𝑏)
• 𝑓𝑓(𝑎𝑎) = 0 = 𝑓𝑓(𝑏𝑏)
Then, there exists a number 𝑐𝑐 ∈ (𝑎𝑎, 𝑏𝑏) such that:
𝑓𝑓 ′ (𝑐𝑐) = 0

Theorem 2.22 (Mean Value Theorem, MVT)


Let 𝑓𝑓 be a function satisfying the following conditions:
• 𝑓𝑓 is continuous on the closed interval [𝑎𝑎, 𝑏𝑏]
• 𝑓𝑓 is differentiable on the open interval (𝑎𝑎, 𝑏𝑏)
Then, there exists a number 𝑐𝑐 ∈ (𝑎𝑎, 𝑏𝑏) such that:
𝑓𝑓(𝑏𝑏) − 𝑓𝑓(𝑎𝑎)
𝑓𝑓 ′ (𝑐𝑐) =
𝑏𝑏 − 𝑎𝑎

REFERENCES:

Leithold, L. (1996). The calculus 7. Boston, United States: Addison Wesley Longman, Inc.

Minton, R. & Smith, R. (2016). Basic calculus. Makati, Philippines: McGraw Hill Education.

02 Handout 1 *Property of STI


Page 11 of 11

You might also like